Chronic treatment with hydroxychloroquine and SARS-CoV-2 infection - Ferreira, A (2020)
Hydroxychloroquine sulfate (HCQ) is being scrutinized for repositioning in the treatment and prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This antimalarial drug is also chronically used to treat patients with autoimmune diseases. By analyzing the Portuguese anonymized data on private and public based medical prescriptions we have identified all cases chronically receiving HCQ for the management of diseases, such as systemic lupus erythematosus, rheumatoid arthritis, and other autoimmune diseases. Additionally, we have detected all laboratory confirmed cases of SARS-CoV-2 infection and all laboratory confirmed negative cases in the Portuguese population (mandatorily registered in a centrally managed database). Cross linking the two sets of data has allowed us to compare the proportion of HCQ chronic treatment (at least 2 grams per month) in laboratory confirmed cases of SARS-CoV-2 infection with laboratory confirmed negative cases. Out of 26 815 SARS-CoV-2 positive patients, 77 (0.29%) were chronically treated with HCQ, while 1215 (0.36%) out of 333 489 negative patients were receiving it chronically (P = .04). After adjustment for age, sex, and chronic treatment with corticosteroids and/or immunosuppressants, the odds ratio of SARS-CoV-2 infection for chronic treatment with HCQ has been 0.51 (0.37-0.70). Our data suggest that chronic treatment with HCQ confer protection against SARS-CoV-2 infection.